Tytuły filmów „oskarowych” w wielojęzycznym przekładzie - Mocarz-Kleindienst, Maria (Acta Polono-Ruthenica, 2018)
This article provides a comparative analysis of translation strategies for the English titles of Oscar-winning movies (Academy Award for Best Picture) into Polish, German and Russian. The titles analyzed show two strategies: adaptation and exotisation. However, they did not show a clear connection between the translation strategy and the degree of linguistic similarity since there was no clear dominance of exotisation in the German versions, considered to be the closest to the original. A significant use of explication of the meaning of the title in German versions was observed, which may indicate an attempt to more accurately convey basic information about a foreign movie to a German viewer.